(untitled) (Revista INTEREDU11, 2021)
Utopianism has been one of the fundamental strategies in pedagogical discourse ever since the modern era. However, in current times which featured by the loss of great story tales, the utopian content in pedagogy seems to be left aside to focus mainly on instructional terms. In the present article, I encourage the reading of the ethical content of “Great Teachers” (Bruns & Luque, 2014), considered a reflection of contemporary pedagogy, where the absence of this traditional strategy is not seen as a synonym of lack of normative content, but a reconfiguration of it, in the same frequency as its socio-political context. In other words, this redefinition may indeed reject utopia, yet not its ethical-political commitments.